Safety and outcomes of 177Lu‐DOTATATE for neuroendocrine tumours: experience in New South Wales, Australia. Issue 10 (10th October 2019) - Lin, Enmoore; Chen, Tina; Little, Alana; Holliday, Laura; Roach, Paul; Butler, Patrick; Hosking, Erika; Bailey, Elizabeth; Elison, Barry; Currow, David
Abstract: Background: Peptide receptor radionuclide therapy with 177 Lu‐DOTATATE is a promising treatment for inoperable or metastatic neuroendocrine tumours (NET). In 2015, the NSW Ministry of Health provided funding for 177 Lu‐DOTATATE treatment of NET under an evaluation framework. Aims: To examine the safety and outcomes of NET patients treated with 177 Lu‐DOTATATE under the evaluation framework and assess the statewide implementation of the NSW Lutate therapy referral and protocol for neuroendocrine cancer patients. Methods: A quality of care clinical audit was conducted on all NET patients treated with 177 Lu‐DOTATATE from October 2010 to October 2015 at St George Hospital, and from August 2013 to March 2017 at Royal North Shore Hospital. Percentage of patients who met protocol selection criteria was calculated. Survival was estimated using the Kaplan–Meier method. Adjusted regression analyses assessed associations between key clinical factors and outcomes. Results: A total of 279 patients was treated. Statewide protocol implementation led to an increase from 60.5 to 83.8% in patients meeting selection criteria. Estimated median overall survival was significantly longer for patients who met selection criteria compared with those who did not (50.7 vs 34.2 months) ( P = 0.018). This was driven by the significantly worse overall survival in patients who failed exclusion criteria ( P < 0.001). 177 Lu‐DOTATATE was well tolerated with haematological, renal and hepatic treatment‐related serious adverse events experienced by 9.7, 0.4 and 0.4% of patients respectively. Conclusions: 177 Lu‐DOTATATE is a promising treatment for advanced NET. Superior survival in patients who met selection criteria emphasise the importance of protocol adherence.